The survival investigation of sonicated soy sauce fermentation yeast strains using a spectrophotometer - Goh, Kok Ming; Lai, Oi Ming; Abas, Faridah; Nyam, Kar Lin; Tan, Chin Ping (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
The present work demonstrated a method to determine the growing activities of typical soy sauce fermentation yeasts under sonication stimulation in stress and/or enriched conditions. The yeast activities were determined using a programmed spectrophotometer which automatically records the optical density (OD) of the growth media. The increasing OD values were directly proportionally to the amount of yeast cells within the growth media. Spectrometry method provides a typical sigmoidal curve with the lag time, maximum growth rate, and average growth rate of microorganisms. Activities of two industrial yeast strains (Zygosaccharomyces spp. and Candida spp.) under sonication stimulations (0.5 cycles, 60 amplitude) at different salt contents (1, 3, and 5%), glucose contents (5, 10, and 15%), sonication durations (10, 20, and 30 min), and incubation temperatures (30 and 37°C) were investigated in a 24-h growth cycle model system by one-factor-at-a-time (OFAT) design. Overall, sonication treatment in the presence of salt was not lethal to yeast cells. The maximum growth rate of both yeast strains was significantly reduced (p < 0.05) when the sample was treated with 5% salt content coupled with sonication. However, when the sample was further enriched with glucose at 10%, it yielded significantly highest growth rate (0.1310 ± 0.0107 OD/h). Finally, 10 min sonication and 30°C incubation temperature were found to be better as compared to the other treatment combinations. Sonication did not exert any detrimental effect on investigated yeasts, and stimulated the growth when enrichment was appropriately provided.